2004
DOI: 10.1111/j.1440-1827.2004.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent expression of CD30 antigen in the primary gastric non‐B, non‐Hodgkin lymphomas

Abstract: Most primary gastric lymphomas are of B-cell origin. Fourteen cases of primary gastric non-B, non-Hodgkin lymphomas were studied to evaluate their clinicopathological and immunophenotypic findings. The cases were comprised of 11 men and three women, with a median age of 56.5 years. Most patients underwent surgery either with or without chemotherapy, exhibiting a 5 year survival rate of 57.5%. Morphologically, the neoplastic cells showed various histological features, such as anaplastic large cell lymphoma (ALC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Such cases usually occur in association with infection by human T‐lymphotropic virus type 1 (HTLV‐1), especially in endemic areas such as Japan. In contrast, rare cases of primary gastric T‐cell lymphoma without HTLV‐1 infection are reported sporadically, but their pathogenesis is still unclear 4–16 . Most cases of primary gastric T‐cell lymphoma consist of large, pleomorphic lymphoma cells with a helper/inducer phenotype, but a minority have MALT lymphoma‐like bland cytological features and a cytotoxic phenotype 4–13 .…”
mentioning
confidence: 99%
“…Such cases usually occur in association with infection by human T‐lymphotropic virus type 1 (HTLV‐1), especially in endemic areas such as Japan. In contrast, rare cases of primary gastric T‐cell lymphoma without HTLV‐1 infection are reported sporadically, but their pathogenesis is still unclear 4–16 . Most cases of primary gastric T‐cell lymphoma consist of large, pleomorphic lymphoma cells with a helper/inducer phenotype, but a minority have MALT lymphoma‐like bland cytological features and a cytotoxic phenotype 4–13 .…”
mentioning
confidence: 99%
“…Primary gastric CD30-positive ALCLs are very rare. There have been several previous reports regarding primary gastric ALCL in Japan and China (6-9); however, to the best of our knowledge, this is the first such reported case in Korea. We can only guess that it is indeed a very rare disease.…”
Section: Discussionmentioning
confidence: 66%
“…ALK-positive ALCL usually occurs at a younger age (15-30 yr), it is a male predominant disease, it exhibits frequent B-symptoms, it is known to be more chemosensitive and to have a better prognosis for survival (14, 15). However, Sachiko et al have reported that one of three patients with gastric CD30-positive ALCL was positive for ALK and EMA (6). In our case, the tumor cells were negative for ALK immunohistochemistry, and the clinical characteristics of our case were in accord with the usual clinical findings for ALK-negative systemic ALCL.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in B cell MALT lymphomas [7], it is also possible that peripheral T cell lymphoma arising from gastric MALT may also have small cell and large cell variants. When the small cell variants transform into large cell variants, they may be associated with CD30 expression [11]. Future cytogenetic and molecular studies may help to further define these rare lymphomas.…”
Section: Discussionmentioning
confidence: 99%